Variability of Rainfall and the Cropping Season of a Tropical Dry Zone River Basin: A Case Study in the Malwathu Oya River Basin in Sri Lanka - Abeysingha, N. S.; Madurapperuma Arachchige, S. D.; Ray, R. L.; Muthuwatta, Lal (Wiley, 2025)
The temporal and spatial rainfall variability impacts water resource management, agricultural productivity, and ecosystem health in river basins. This study utilized 44 years of daily rainfall data (1976–2020) at 27 stations across the Malwathu Oya river basin, Sri Lanka, to investigate the temporal and spatial variability of rainfall in the basin and identify possible impacts of climate change on rainfall variability and trends. Standardized anomaly, coefficient of variation (CV), monotonic trends of rainfall and dry days, and the onset and retreat of the cropping season, Maha were computed for the last four decades, and the impacts of climate change were evaluated by checking the differences in the variables before and after the year 2000 using the Wilcoxon signed-rank test. The annual rainfall of the Malwathu Oya river basin shows a significant increase, primarily contributed by the upstream region. The study identified the higher variability of the onset of the Maha seasonal rainfall, showing an early onset of the season. Total annual rainfall showed a significant increase after the year 2000, probably due to climate change, and the overall temporal patterns of rainfall events remain consistent with those of before 2000. This trend toward more intense but less frequent rainfall events highlights the need for adaptive water resource management plans to mitigate potential challenges related to flood risks in the basin, and the early onset of Maha rain is to be taken as an opportunity for the farmers in the basin.